Evaluation of the neurosensory function of the medial meniscus in humans - KARADAĞ SAYGI, NAİME EVRİM (W B SAUNDERS CO-ELSEVIER INC, 2005)
Purpose: Menisci are known to have receptors mainly concentrated at the anterior and posterior horns. Although they are purported to send afferent impulses to the central nervous system, this function has not been thoroughly evaluated. The purpose of the study was to investigate whether stimulation of the menisci initiates a cortical response. The reaction of the end organ to the reflex are is also evaluated. Type of Study: Prospective case series. Methods: Fourteen patients with normal medial menisci were included in the study. Different parts of the knee joint (the posterior horn and the body of the medial meniscus, the medial femoral condyle, the capsule, and the joint space) were electrically stimulated by a probe during arthroscopy. The cortical response was monitored with somatosensory-evoked potentials (SEPs). The compound muscle action potentials (CMAPs) of the semi membranosus, quadriceps, and biceps femoris muscles were also monitored with electroneuromyography (ENMG). Results: Among the stimulated parts, only the posterior horn of the meniscus produced cortical responses. No response was obtained with stimulation of the medial femoral condyle, the body of the medial meniscus, the capsule, or the joint space. Stimulation of the posterior horn of the medial meniscus produced a measurable amount of CMAP latency for the semimembranosus muscle, but not for the quadriceps and biceps femoris muscles. Conclusions: Stimulation of the posterior horn of the medial meniscus produces reproducible cortical SEPs and results in ENMG-verified response of the semimembranosus muscle where no response of the sernimembranosus muscle is detected with stimulation of the other parts of the knee. Clinical Relevance: The knowledge that only the horns of the medial meniscus have mechanoreceptors in the medial compartment of the knee helps to understand patients' signs and symptoms in medial compartment disease.
Keywords: meniscus; somatosensory evoked potentials; electroneuromyography; neurosensory; semimembranosus; ANTERIOR CRUCIATE LIGAMENT; KNEE; MECHANORECEPTORS; INNERVATION; JOINT